ANALISIS KESALAHAN PENGGUNAAN KALIMAT “BA” DAN “BEI” PADA MAHASISWA PRODI PENDIDIKAN BAHASA MANDARIN ANGKATAN 2019 FKIP UNTAN - Ashri Amalia Pandhita; Ina Ina; Yoanna Afrimonika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
In Mandarin, many words are used differently from other languages, some even doesn’t exist in other languages, one of which is the prepositions "ba" and "bei". Both of these preparations are often used in Chinese, but because they have special ways of use, students often use them wrongly . The author gave a test on "ba" and "bei" to students of Tanjung Pura University in 2019 Chinese language education study program, the goal is to find out the students' knowledge and difficulties. From the results of this test, the author found that many students experienced errors when using the sentence with "ba" and "bei", this proves that many of them lack the understanding of prepositions "ba" and "bei". For that, it is necessary to give a deeper lesson about "ba" with "bei", so that it can minimize errors that may occur.